2021
DOI: 10.1101/2021.07.02.450839
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protein abundance and folding rather than the redox state of Kelch13 determine the artemisinin susceptibility of Plasmodium falciparum

Abstract: Decreased susceptibilities of Plasmodium falciparum towards the endoperoxide antimalarial artemisinin are linked to mutations of residue C580 of Kelch13, which is the homologue of the redox sensor Keap1 in vertebrates. Here, we addressed whether mutations alter the artemisinin susceptibility by modifying the redox properties of Kelch13 or by compromising its native fold or abundance. Using selection-linked integration and the glmS ribozyme, efficient down-regulation of Kelch13 resulted in ring-stage survival r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 57 publications
2
1
0
Order By: Relevance
“…ART-resistance, measured by RSA, decreased as the rapalog concentration and hence K13 knock sideways decreased, confirming that RSA-survival is a function of K13 levels in the parasites (Figure 3C). These results confirm observations made on parasites in which the K13 abundance was titrated on mRNA level through the glmS system (19). To confirm that this was due to a reduction in endocytosis, we performed a second titration using KIC7, a K13-compartment protein, which was also knocked aside using the same decreased rapalog concentrations as for K13 (Figure 3D).…”
Section: Cellular Levels Of K13 and Kic7 Proteins Determine Art-resis...supporting
confidence: 86%
See 2 more Smart Citations
“…ART-resistance, measured by RSA, decreased as the rapalog concentration and hence K13 knock sideways decreased, confirming that RSA-survival is a function of K13 levels in the parasites (Figure 3C). These results confirm observations made on parasites in which the K13 abundance was titrated on mRNA level through the glmS system (19). To confirm that this was due to a reduction in endocytosis, we performed a second titration using KIC7, a K13-compartment protein, which was also knocked aside using the same decreased rapalog concentrations as for K13 (Figure 3D).…”
Section: Cellular Levels Of K13 and Kic7 Proteins Determine Art-resis...supporting
confidence: 86%
“…We found that the amount of K13 and KIC7 at the K13 compartment in the cell determine the level of in vitro resistance, confirming that the endocytic process is important for ART resistance and suggesting that the amount of protein directly influences the rate of endocytosis and level of ART susceptibility. The same effect on resistance was observed in a k13 mRNA titration recently (19) and a role of K13 protein abundance rather than a specific functional change in resistance is also supported by the finding that increasing levels of K13 C580Y reverts resistant parasite back to sensitive (10). The finding that KIC7 titration had a similar effect strengthens this conclusion and further supports that resistance is due to altered endocytosis levels.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation